In an Age of Heritage Signs, Encouraging Archaeological Sites to be Cosmopolitan Canopies. Issue 1 (27th September 2019) - Baram, Uzi
To mark history, governments authorize the erecting of markers, signs on the landscape meant to inform. While historical markers have a long tradition for identifying places with significant events and people, there has been an expansion on what and how to mark places and their heritage. Signs capture the attention and provide information for those interested in learning about where they are at the moment. They are in-situ teaching tools, open to anyone able to interpret the heritage for broad audiences, and can encourage places for cosmopolitanism, canopies for people to learn about the past and each other.